Rosacea associated with increased risk of generalized anxiety disorder: a case-control study of prevalence and risk of anxiety in patients with rosacea, - Pinar Incel Uysal; Neslihan Akdogan; Yildiz Hayran; Ayse Oktem; Basak Yalcin (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Rosacea may result in emotional distress and anxiety. However, data on the presence of generalized anxiety disorder in rosacea patients are scarce. Objective: The aim of the study was to detect the frequency and level of anxiety and depression in patients with rosacea. Methods: A total of 194 consecutive rosacea patients and 194 age- and sex-matched controls were enrolled. Severity of rosacea was assessed in patients according to the criteria of the National Rosacea Society Ethics Committee. Both patients and controls were evaluated by the Generalized Anxiety Disorder 7-item scale, and severity was measured by the Generalized Anxiety Disorder-Adult. Results: Individuals who were diagnosed with an anxiety and/or depressive disorder were more common in patient group (24.7% vs. 7.2%, p < 0,01). Female patients were particularly at risk for having generalized anxiety disorder (OR = 2.8; 95% CI 1.15-7.37; p = 0.02). Study limitations: Single center study and limited sample size. Conclusions: Rosacea patients show greater risk of having anxiety disorders, including generalized anxiety disorder. Female patients, those with lower educational levels, those with phymatous subtype, untreated patients, and patients with prior psychiatric morbidity may be at particular risk for anxiety. It is essential to consider the psychological characteristics of patients to improve their well-being.